2013
DOI: 10.1016/j.ces.2013.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Experiments and modelling of a draft tube airlift reactor operated at high gas throughputs

Abstract: Study and modelling of an annular sparged draft tube airlift at high gas throughputs. Strong influence of collective effects and flow pattern on the riser hydrodynamics. Weak effect of gas volume fraction increase on bubble's mass transfer coefficient. Volumetric mass transfer coefficient is proportional to the gas superficial velocity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The value of Sh of the bubbles (d 32 < 1.5 mm) can be approximately predicted by Frosslingʼs equation with an average relative deviation of 34.3%. Although it has been reported that the mass transfer model developed based on a single bubble was applied to predict the k L of bubble swarms, 13,84 numerous investigations have indicated that the discrepancy between the mass transfer coefficient of a single bubble and bubble swarm cannot be neglected. 42,[85][86][87][88] Fig.…”
Section: Mass Transfer Characteristicsmentioning
confidence: 99%
“…The value of Sh of the bubbles (d 32 < 1.5 mm) can be approximately predicted by Frosslingʼs equation with an average relative deviation of 34.3%. Although it has been reported that the mass transfer model developed based on a single bubble was applied to predict the k L of bubble swarms, 13,84 numerous investigations have indicated that the discrepancy between the mass transfer coefficient of a single bubble and bubble swarm cannot be neglected. 42,[85][86][87][88] Fig.…”
Section: Mass Transfer Characteristicsmentioning
confidence: 99%
“…While such approaches give a high degree of insight into the process, they can only be applied at relatively low superficial velocities. Due to the experimental difficulties involved, most published studies [4,[6][7][8][9][10][11] have instead reported the product of these quantities, that is, the volumetric mass transfer coefficient (k L a). For systems operated at superficial velocities up to 0.1 m s À1 k L a values in the range of 0.01-0.1 s À1 have been reported, with values varying based on the column configuration, liquid phase used and of course the superficial velocity.…”
Section: Introductionmentioning
confidence: 99%